Analisis Kebijakan Corporate Social Responsibility PT Telkom Indonesia dalam Upaya Peningkatan Ekonomi Nasional - Nisa Masitho; Agustine Rossa Diah Utari (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
This research discusses legal certainty in the implementation of Corporate Social Responsibility (CSR) in a normative and conceptual review. An important point in this research is the context of differences in different mechanisms in implementing CSR between State-Owned Enterprises (BUMN), especially PT Telkom Indonesia and private companies which do not have a unified understanding of CSR. This research uses a normative research type with a statutory and conceptual approach supported by legal materials in it. This research consists of two problem formulations, namely 1) How do CSR arrangements in Indonesia improve the national economy? 2) What is the impact of PT Telkom Indonesia's CSR policy on the national economy? This gives rise to two conclusions, namely 1) There is a gap in the implementation of CSR between BUMN and the private sector due to differences in interpretation therein. 2) CSR has a positive impact on society, but of course requires optimization in its implementation. PT Telkom Indonesia is listed as a company with the best CSR management with various awards received.